2023
DOI: 10.38204/atrabis.v9i1.1007
|View full text |Cite
|
Sign up to set email alerts
|

Produktivitas Dosen Dalam Pelaksanaan Tri Dharma Perguruan Tinggi (Studi Pada Sekolah Tinggi Teknologi YBSI Tasikmalaya)

Abstract: Produktivitas dosen merupakan  suatu  hal  yang  sangat  penting  di lembaga perguruan  tinggi  dalam  upaya  untuk  mencapai  tujuanya.  Khususnya dalam kaitannya dengan pelaksanaan Tri Dharma Perguruan Tinggi yaitu pelaksanaan pendidikan dan pengajaran, penelitian dan pengabdian pada masyarakat. Hal ini termasuk pula di lembaga STT YBSI Tasikmalaya.  Tujuan Penelitian ini adalah ;1)Untuk mengetahui dan mendeskripsikan produktivitas dosen di Lembaga Pendidikan STT YBSI Tasikmalaya dalam pelaksanaan tri dharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It can be concluded that the Prisma Information System fully supports the submission of service research proposals, a faster and easier process, safer data and guaranteed credibility, dynamic configurability, more responsive design, and assistance documentation, as well as other new features. lecturers can provide benefits and be felt by the community (Budiman, 2023;Fitriana et al, 2021;JRS & Sitinjak, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the Prisma Information System fully supports the submission of service research proposals, a faster and easier process, safer data and guaranteed credibility, dynamic configurability, more responsive design, and assistance documentation, as well as other new features. lecturers can provide benefits and be felt by the community (Budiman, 2023;Fitriana et al, 2021;JRS & Sitinjak, 2023).…”
Section: Introductionmentioning
confidence: 99%